2023
DOI: 10.3390/su151511975
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Helical Piles and Granular Anchor Piles for Foundation Stabilization in Expansive Soil: A 3D Numerical Study

Abstract: This study investigates the performance of granular anchor piles and helical piles in expansive soils. Expansive soils pose challenges for engineering due to their significant swelling and shrinkage characteristics. Special considerations are required for constructing foundations on expansive soil to mitigate volumetric changes. While helical piles provide uplift resistance in light structures, they may not fully stabilize foundations in expansive soils. In contrast, granular anchor piles offer a simpler alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The present study follows a methodology similar to that of Alnmr et al [94,95]. Figure 15 provides a cross-sectional view of reinforced soil featuring helical piles.…”
Section: Methodsmentioning
confidence: 99%
“…The present study follows a methodology similar to that of Alnmr et al [94,95]. Figure 15 provides a cross-sectional view of reinforced soil featuring helical piles.…”
Section: Methodsmentioning
confidence: 99%
“…The primary application of the soil-water characteristic curve (SWCC) is to evaluate the performance of unsaturated soil properties for a range of geotechnical engineering applications [1]. One common application of SWCCs in geotechnical engineering is to assess the hydraulic properties necessary to simulate water flow through unsaturated soils [2][3][4][5][6]. The SWCC shape reflects the soil's water retention capacity and porosity characteristics, enabling the estimation of various engineering properties such as hydraulic conductivity, shear strength, and diffusion coefficient [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nelson and Miller [7] assert that expansive soils may result in greater financial losses than earthquakes or floods. In addressing this challenge, the behavior of expansive soils has been studied in numerous studies by adding different materials to improve their characteristics [8][9][10][11][12][13][14][15]. Although these studies have shown that soil characteristics can be improved via the addition of materials, many unresolved questions remain.…”
Section: Introductionmentioning
confidence: 99%